Integration gaps persist despite immigrants’ value assimilation: evidence from the European Social Survey - Suárez, Jorge; Hannikainen, Ivar R. (Frontiers in Sociology, 2025)
In Europe, although integration of the immigrant population is acknowledged as a multidimensional challenge, the precise dimensions of integration have varied considerably throughout the past decades and between nations. Nowadays, most states have adopted ‘civic integration’ programmes to some extent, thereby placing weight on the acquisition of ‘national moral values’, implying that successful integration requires the assimilation of certain core values and implementing various strategies to instil these in immigrants. However, critics of civic integration have called into question whether the adoption of a host society’s normative values facilitates immigrants’ own integration. To provide evidence on this matter, we leverage data from the European Social Survey, collected between 2002 and 2020 (N = 261,830) and examine how immigrants’ self-reported values relate to their integration. Our analyses ask whether value assimilation predicts improvements in immigrants’ occupational status, socialization, and political participation throughout 27 countries in the European Union. We find that differences in moral values account, at most, for a fraction of the integration gap between natives and immigrants. These results therefore call into question the assimilationist principle that adopting a host society’s values is conducive to immigrants’ integration.